Graph structures for knowledge representation and reasoning : 5th International Workshop, GKR 2017, Melbourne, VIC, Australia, August 21, 2017, Revised selected papers /: 5th International Workshop, GKR 2017, Melbourne, VIC, Australia, August 21, 2017, Revised selected papers. (2018) - Unknown
No abstract available